Move analysis of results-discussion chapters in TESOL Master’s theses written by Vietnamese students - Loan Thi Thuy Nguyen,; Issra Pramoolsook, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
Results and Discussion chapters are considered difficult to write in a thesis, especially for non-native English writers. However, few studies have been conducted on how writers compose these two genres. This study, therefore, explores the move-step structures of these two chapters in 24 Master’s theses written by Vietnamese postgraduates. Based on the framework by Chen and Kuo (2012) and the discourse-based interviews with actual thesis writers and supervisors, the study found that this group of writers constructed the genres according to their perceived communicative purposes of these chapters. Moreover, the presence of section/chapter introduction-next section/chapter introduction-section/chapter summary cycles tends to reflect the distinctive composition of these texts at the TESOL discourse community in Vietnam. These findings suggest that explicit instructions on rhetorical structures of these two genres should be provided to non-native English writers and attention should also be paid to specific practice of a genre composition in a particular discourse community.